Profile of Neonatal sepsis - Khinchi, YR; Kumar, Anit; Yadav, Satish (Journal of College of Medical Sciences-Nepal, 2010)
Objective: To study the clinical presentation, investigational profile and outcome of neonatal sepsis in general and with special reference to inborn (intramural) or out born (extramural), sex and weight of the neonate. Materials and method: Retrospective descriptive study of neonates admitted during 2 years from July 2007 to June 2009 in special care neonatal unit of the department of Pediatrics, College of Medical Sciences-Teaching Hospital, Bharatpur, Nepal. Results: Majority of neonates were out born and referred (72.2%) to this institution. Significant number of babies was having sepsis in out born group (59%) as compared to inborn (35%). Male sex was found to have more sepsis as compared to female. Sepsis was observed to be inversely related to birth weight, 65% in low birth weight (LBW, <2.5Kg) as compared to 42.6% in normal birth weight group (> 2.5kg). Conclusions: High index of suspicion for diagnosis of neonatal sepsis is required especially in the presence of risk factors. Prevalence of sepsis is inversely related to birth weight. More number of out born delivered babies developed sepsis. Neonatal sepsis related morbidity and mortality can be significantly reduced by comprehensive obstetric and neonatal care at multiple levels right from community to health institutions. Key words: Neonatal sepsis; Inborn; Out born; Low birth weight (LBW). DOI: 10.3126/jcmsn.v6i2.3609 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 1-6